ANALISIS KINERJA KEUANGAN PT ASURANSI BINA DANA ARTA (ABDA) TBK SEBELUM, MASA TRANSISI, DAN SETELAH ADANYA BPJS KESEHATAN PERIODE 2010-2019 - Zakaria Hamzah, Zeze; Osta Nababan, Benny; Satria Rukmana, Heru; Nur Fatimah, Siti (Economicus, 2022)
ABSTRACT This study aims to determine whether there are differences in the financial performance of the company PT Asuransi Bina Dana Arta (ABDA) before (2010-2013 period), during the transition period (2014-2015 period), and after (2016-2019 period) the implementation of BPJS Kesehatan. The analysis technique used is Financial Ratio Analysis and Trend Analysis. This study uses a type of comparative research with a quantitative approach, using data collection techniques through documentation and literature study. The location of this research is by means of a desk study using data published on the Indonesia Stock Exchange (IDX) through www.idx.co.id, the company's official website www.abdainsurance.co.id and www.bpjs-kesehatan.go.id. While the time of this research starts from February 2021 to October 2021. The results showed that PT Asuransi Bina Dana Arta (ABDA) Tbk when viewed from the analysis of Liquidity showed a stable condition, Solvency improved, but from the analysis of Activity and Profitability showed a decrease. So it can be concluded that the trend that occurred after the BPJS Health showed a trend line that experienced more decline. To improve and maintain its existence, PT Asuransi Bina Dana Arta (ABDA) Tbk can provide benefits in the form of more facilities to its participants that cannot be obtained from BPJS Health, or collaborate with BPJS Health to implement the COB (Coordination Of Benefit) principle.